2023
DOI: 10.1002/slct.202204629
|View full text |Cite
|
Sign up to set email alerts
|

iAMY‐DC: Identifying Amyloid Proteins by Using Dynamic Correlation Features

Abstract: Recent studies reported that amyloid proteins keep a closely relationship with some common diseases, such as Alzhemier's disease, Parkinson's disease, and type 2 diabetes. In view of this, it is an urgent task to discriminate amyloid proteins from non‐amyloid proteins. In this work, we developed a new machine learning model to identify amyloid proteins based on the sequence information. Firstly, fifty different kinds of physicochemical (PC) properties were employed to denote sequences. Then, a sliding window a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We also conduct a comparative evaluation of the proposed model in this study with established models that have demonstrated high performance. Since the Web site provided in the RFAmyloid paper was unavailable, we selected iAmyS cm, BioSeq_SVM, BioSeq_KNN, BioSeq_RF, BioSeq_CD, AmyPred-FRL, and iAmy-DC as the established models for comparison. All the models, including the proposed method and the four established models, are tested on the same data set taken from the CPAD 2.0 database.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also conduct a comparative evaluation of the proposed model in this study with established models that have demonstrated high performance. Since the Web site provided in the RFAmyloid paper was unavailable, we selected iAmyS cm, BioSeq_SVM, BioSeq_KNN, BioSeq_RF, BioSeq_CD, AmyPred-FRL, and iAmy-DC as the established models for comparison. All the models, including the proposed method and the four established models, are tested on the same data set taken from the CPAD 2.0 database.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, all algorithms concentrate solely on the utilization of features but neglect the interactions between amino acids that originate from their physicochemical differences in real-world scenarios. While iAMY-DC gauges the correlations among features within windows by deploying a sliding window method in conjunction with the Pearson correlation coefficient, it still only considers local information and relies on statistical techniques without accounting for the potential interactions between amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation